Healthcare professional’s moral distress during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
Background: the COVID-19 pandemic brought several moral conflicts in the healthcare context. The impossibility to act in a way that the professionals consider ethically correct, due to external or internal barriers, can trigger moral distress. This phenomenon is prejudicial to the professional’s morals and can impact the quality of care provided. Objective: to analyze which circumstances, during the COVID-19 pandemic, cause moral distress in healthcare professionals. Methods: this integrative review of the literature was made in the SCIELO and PubMed databases, based on the descriptors “moral distress” and “COVID-19”. Articles published between 2019-2021, in Portuguese, Spanish and English were included. PRISMA criteria were followed. Results: from an initial search of 171 documents, 102 were completely reviewed and 29 were included in this review. The causes of moral distress in healthcare professionals can be distributed in the following categories: personal; patients and caregivers; team; organization. Lack of resources, intermittent treatments, fear of contracting the virus, visit restrictions, and absence of explicit guidelines were some events mentioned by the articles. Conclusion: the pandemic caused by COVID-19 has been causing moral distress among professionals. This phenomenon can bring serious consequences for the health of professionals and the care provided by them. Education and support programs, in addition to further studies, should be encouraged to minimize the impact in the next stages of the pandemic and on future occasions related to ethical dilemmas.